Psycho-demographic factors as predictors of depression among person with diabete mellitus (2016)
The study examined psycho-demographic factors as predictors of depression among persons with diabetes mellitus in Ibadan metropolis. A cross-sectional survey method was adopted to collect data from two hundred and thirty eight respondents with one hundred and fifteen (48.3%) males; and one hundred and twenty-three (51.7%) females and age ranging from 17 - 74 years with mean (x) 44.3 years and standard deviation (SD) 12.1. The result of regression analysis suggested that hopelessness, life purpose, and gender were significant independent predictors of depression, while the variables jointly predicted depression; R =.44; F (7,237) = 8.12; P < .005. Also, the variables jointly accounted for 17% (Adj. R2 = .174) variance on the depression. Low life purpose has a significant influence on depression (t = 3.48; P <.05). In conclusion, the study found that the above psycho-demographic variable has significant influence on depression. Therefore, it was recommended that government, and non-governmental organizations should create more public awareness on the possible effect of those variables that was found to have negative influence on depression in our society.